Pengenalan Berbagai Profesi Guna Memantapkan Cita-Cita Anak Sejak Dini di SD Negeri 50 Kota Palembang - Cahya, Gemala; Saadah, Raudhatus; Zikri, Ahmad; Niati, Sri Murda; Anzar, Erniati (Penerbit Goodwood, 2024)
Purpose: The aim of this article is to provide education to students on the importance of establishing goals from an early age. Aspirations can be determined if students already know about various professions. The types of work that require education and special skills are known as professions. Therefore, many children do not prepare for what they will become in the future. Methodology/approach: The strategy used to provide knowledge regarding the introduction of various professions is to give direct lectures about various professions, equipped with their advantages and abilities that must be possessed and prepared from an early age. Results/findings: Through discussions with participants, the service team received information that, on average, students only knew about their profession, but did not yet know how to achieve these goals. In addition, many students still do not know the profession of private employees such as company supervisors or BUMN employees. They know only the professions they often see, such as teachers, doctors, police, and traders. This was discovered during the question-and-answer discussions during socialization. Explained the material from the head of service explaining the abilities that must be possessed if students want to become people in this profession Limitation: This service still needs to be improved with further activities to provide more enthusiasm so that children can be enthusiastic about pursuing their dreams Contribution: We would like to express our gratitude for the assistance and cooperation from SD Negeri 50 Palembang for the permission given to the community service team.